The Impact of Digitalization on Management Accounting and Business Decision Quality - Usman, Asri; Alimuddin, Alimuddin; Darmawan, Alif Isyawatul; Fadhilati, Dzul (Universitas KH. Abdul Chalim Mojokerto, 2026)
Companies and MSMEs must increase their capacity to make more adaptive and effective strategic and tactical decisions in response to developments in the digital world. This study examines how management accounting and management information systems (MIS) work together to make good business decisions in the digital age. The method used is a literature study, or literature review, conducted by searching for relevant scientific articles using a qualitative approach. The results of the review show that management accounting not only serves to record and control costs but also as a strategic tool that provides relevant, timely, and accurate information for decision makers. It has been proven that high-quality MIS can accelerate processes, improve data accuracy, reduce operational costs, and increase company competitiveness. The synergy between digital technology and management accounting enables more logical, effective, and responsive decision-making in response to changes in the business environment. However, its implementation is highly dependent on ready infrastructure, qualified human resources, and a supportive corporate culture. This study shows that digital transformation enhances the contribution of management accounting in strategic and tactical decisionmaking, although issues such as fear of change and system problems still need to be addressed.